INTER-RELIGIOUS TOLERANCE IN INDONESIA: : A Case Study Of Tolerance Between Religious Communities in Getas Temanggung Community In 1968-2022 - Setyaningsih, Wahyu; Khamid, Nur; Aulia, Akhlis; Trisnawati, Diana (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
Various religions that grow and develop in Getas Temanggung cause the importance of tolerance awareness owned by each individual. Tolerance is the key to harmonizing life amid a whirlpool of differences. Without tolerance, the nation will be disintegrated. This study aims to analyze the socio-religious conditions of the Getas Community and analyze the dynamics of tolerance between religious people of the Getas Community. This research method uses case studies with a freedom of religion and belief approach. This research contributes to supporting the realization of unity and invites readers to have an awareness of tolerance in life, differences are grace not solvers. The findings of this study show the tolerance of the Getas Society by Rainer Forst's concept of tolerance theory, namely respect conception. The awareness of tolerance can be realized because of the idea of Surat Al Kafirun verse 6 which means for you your religion. For me, my religion has become the foundation of life in daily social interactions. Many people convert due to economic and marriage factors. However, they still live in harmony. The establishment of houses of worship that coexist between different religions. In Getas there are already 33 houses of worship from four religions. The construction of houses of worship is carried out collaboratively with the community regardless of religion. Various celebrations of religious holidays and traditions are carried out interreligious. In addition, tolerance has become the soul of society within the family sphere. Because many of a family consists of family members from various religions and live in harmony.